Study Of Heat Pump Drying System - Lim, Wan Lynn (2020)
Drying clothes outdoor is slowly becoming an obsolete option as more people are living in condominiums and sunlight reaching the drying area is not sufficient. The urbanized living soon may require a clothes dryer as essential household equipment. The major problems with the commercial clothes dryer are the high power consumption and the possible damage to the environment. Hence, this project aims to mitigate these issues with an eco-friendly heat pump clothes dryer. The heat pump principle is derived based on the waste heat that comes out from the condenser side of the indoor air conditioner units. The heat pump clothes dryer utilizes waste heat from the air conditioner to dry clothes, so no extra heat is produced and no electricity is needed to run it. A portable air conditioner, rather than a split unit air conditioner, is used in the project. The air properties were measured to assess the shift in drying properties. The study proves the application of heat pump clothes dryer as a replacement for the current drying methods. It can dry faster by approximately 3 hours compared to outdoor drying at the balcony. It also shows the impact of temperature setting for the portable air conditioner on the drying time of clothes. The users will not face a significant difference in the drying time of 1.5 hours for 1 kg of clothes when they change the temperature setting throughout the day. The suitable clothes load for the heat pump clothes dryer was attained to note the strength of the heat source supplied from a portable air conditioner. The users can dry up to 1.5 kg of clothes for over 3 hours. The users may need to use the dryer more frequently or a longer time to clean their weekly laundry load if they switch on the portable air conditioner for a shorter time. Also, the study exhibits that the drying rate will be much faster when the inlet is completely sealed rather than partially sealed. The target of this study ultimately is to evaluate the performance of such a drier and analyze its potential as a competitor to the commercial clothes dryer.